Prevalencia de los espacios primates en niños de 5 a 7 años de edad que acuden a Escuela Fiscal Mixta Gustavo Jaramillo, a la Unidad Educativa Ludoteca y a la Clínica Odontológica Integral de la UDLA. - García Bazante, María Fernanda (2017)
The primate spaces are normal and important physiological spaces in the dentition Decidua, located in the maxilla, between the lateral and the canine, and in the mandible between the canine and the first temporal molar, these have particular importance in the change of the dentition of Decidua to definitive for a correct alignment in the dental arches during the eruption of the definitive teeth. Objectives: this is why the purpose of this study is to determine the prevalence of primate spaces, for this, an observational descriptive cross-sectional investigation was carried out in 150 children from 5 to 7 years of age who attend two educational centers and the dental Clinic of the University of the Americas, in the period march from 2017 to April of 2017; Results: It could be known that there is a prevalence of 25.3 percent of the cases that present this particularity, in terms of gender, there was greater prevalence of primate spaces in children with respect to girls, without making significant difference; Likewise it was observed that both genera present the same relationship of absence in the jaws being more frequent than the presence, this makes us think that both genders could suffer in the same way alterations in the alignment of the permanent teeth, bringing consequences of anterior or posterior crowding, and bad future occlusions of the permanent teeth.